Magnetic Properties Evaluation of Fe-Al Nanocrystalline Alloys Fabricated by Mechanical Alloying Technique as a Function of Milling Time - Tarigan, Kontan; Ginting, Masno (Teknologi Indonesia, 2012)
Magnetic properties of nanocrystalline Fe50Al50 alloys prepared by mechanical alloying technique (using commercial Fe and Al powders as precursors) were studied in detail as a functions of the milling time ranging from 1 to 24 hrs. The structural analyses based on X-ray diffraction (XRD) and extended X-ray absorption fi ne structure spectroscopy (EXAFS) revealed that the alloying process took place after 12 hrs of milling time. Concerning themagnetic behavior, the data that were obtained from a superconducting quantum interference device (SQUID) showed that both the magnetic saturation (Ms) and the coercivity (Hc) depend strongly on the milling time. From the results that we obtain, we found out that by adjusting the milling time, is a key factor in obtaining an appropriate structural transformation and appropriate magnetization values.